2020
DOI: 10.1002/jcp.29896
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acid adenine dinucleotide phosphate activates two‐pore channel TPC1 to mediate lysosomal Ca2+ release in endothelial colony‐forming cells

Abstract: Nicotinic acid adenine dinucleotide phosphate (NAADP) is the most recently discovered Ca 2+-releasing messenger that increases the intracellular Ca 2+ concentration by mobilizing the lysosomal Ca 2+ store through two-pore channels 1 (TPC1) and 2 (TPC2). NAADP-induced lysosomal Ca 2+ release regulates multiple endothelial functions, including nitric oxide release and proliferation. A sizeable acidic Ca 2+ pool endowed with TPC1 is also present in human endothelial colony-forming cells (ECFCs), which represent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 99 publications
6
46
0
Order By: Relevance
“…Taken together, these findings endorse the view that TRPV4‐mediated extracellular Ca 2+ entry is required to initiate InsP 3 ‐dependent intracellular Ca 2+ oscillations. A recent report showed that NAADP‐induced EL Ca 2+ release through TPC1 supports oscillations in [Ca 2+ ] i mediated by InsP 3 Rs in ECFCs 14 . In agreement with these observations, hAFS‐CM Hypo failed to trigger cytosolic Ca 2+ signals in the presence of the lysosomotropic compound, GPN (200 µmol/L, 30 minutes), 36,37 and of NED‐19 (100 µmol/L, 30 minutes), a selective TPC antagonist 38,39 .…”
Section: Resultssupporting
confidence: 70%
“…Taken together, these findings endorse the view that TRPV4‐mediated extracellular Ca 2+ entry is required to initiate InsP 3 ‐dependent intracellular Ca 2+ oscillations. A recent report showed that NAADP‐induced EL Ca 2+ release through TPC1 supports oscillations in [Ca 2+ ] i mediated by InsP 3 Rs in ECFCs 14 . In agreement with these observations, hAFS‐CM Hypo failed to trigger cytosolic Ca 2+ signals in the presence of the lysosomotropic compound, GPN (200 µmol/L, 30 minutes), 36,37 and of NED‐19 (100 µmol/L, 30 minutes), a selective TPC antagonist 38,39 .…”
Section: Resultssupporting
confidence: 70%
“…Two‐pore channels (TPC) 2 have been reported to be one of the TPCs which could be triggered via NAADP to release calcium from endolysosomal organelles 23‐25 . Moccia et al found that NAADP‐induced TPC1‐mediated Ca 2+ release can selectively be recruited to induce the Ca 2+ response to specific cues in circulating ECFCs 26 . The expression of TPC1/2 within PASMCs of rats has been proven in our previous study, with TPC1 being the dominant subtype 27 .…”
Section: Introductionsupporting
confidence: 54%
“…Stimulating endothelial cells with VEGF has been reported to promote IP3 production and activate the endothelial Ca 2+ signals 27 . Moreover, NAADP‐induced TPC‐mediated Ca 2+ release is critical for VEGF‐induced angiogenesis 26,28 . To investigate the possibility that NAADP was involved in PAEC angiogenesis, PAECs were stimulated with VEGF and NAADP; the angiogenesis of PAEC was subsequently monitored.…”
Section: Resultsmentioning
confidence: 99%
“…NAADP activates endothelial TPCs to induce the global Ca 2+ signals which control NO release and blood pressure (Brailoiu et al, 2010c), secretion of von Willebrand factor (vWF) and platelet aggregation (Esposito et al, 2011), neurovascular coupling (Negri et al, 2019;Zuccolo et al, 2019b;Berra-Romani et al, 2020), angiogenesis (Favia et al, 2014) and vasculogenesis (Zuccolo et al, 2016;Di Nezza et al, 2017). A recent investigation confirmed that, also in the endothelial lineage, NAADP-induced Ca 2+ release through TPCs may be amplified into regenerative intracellular Ca 2+ oscillations by the Ca 2+ -dependent recruitment of InsP 3 Rs (Moccia et al, 2020b).…”
Section: Basic Insights Into El Ca 2+ Signaling: the Role Of Tpcs In The Cardiovascular Systemmentioning
confidence: 97%
“…However, an increase in EL pH also represents a widely employed strategy to deplete the EL Ca 2+ store, as intraluminal Ca 2+ reloading impinges on the proton-motrive force (Morgan et al, 2011;Faris et al, 2018). Furthermore, bafilomycin A1, which causes an increase in EL pH by inhibiting the v-ATPase activity and discharging the EL Ca 2+ pool (Faris et al, 2019;Moccia et al, 2020b), may also reduce MERS-CoV infection in vitro (Gunaratne et al, 2018a). Therefore, TPC-mediated EL Ca 2+ mobilization may be regarded as a crucial regulator of MERS-CoV entry in host cells.…”
Section: Tpcs Mediate Entry and Trafficking Of Viruses In Host Cellsmentioning
confidence: 99%